The Effect of Plyometric Training on Developing Explosive Power Specific to Jump Shooting in Handball – An Experimental Study - BENYAHIA, Oussama; SEFIR, Hadj; CHERIET, Mohamed El Hacène El Maamoun; BENAISSA, Redha; HADDI, Ali; BELDJOUHEUR, Fayçal; KHELLAFI, Aziz; BENSAADA, Maamar Badreddine (Journal of Ecohumanism, 2026)
This comprehensive study aims to investigate the profound impact of plyometric training on developing muscular capabilities—specifically explosive power—and its direct correlation with enhancing the biomechanical and skill execution of the high jump shot among youth handball players (aged 17–19 years). Given the precise nature of the research problem, a rigorous experimental methodology was adopted. The sample comprised 20 elite youth players from the Boukadir and Oued Sly teams, distributed purposefully and equally into a control group and an experimental group, while goalkeepers were deliberately excluded due to their divergent biomechanical requirements.1 The experimental group underwent a highly periodized, 7-week plyometric program consisting of 14 training units. The statistical analyses yielded statistically significant superiority for the experimental group across all physical assessments (Sargent vertical jump, 3kg medicine ball push, 30-second incline pushups, and the 3-step jump) as well as skill-based execution (jump shooting from outside the 9-meter zone). These findings unequivocally establish the efficacy of mechanically deploying the Stretch-Shortening Cycle (SSC) to recruit high-threshold motor units. This neural optimization translates directly into elevated kinematic explosive power, enabling athletes to bypass and conquer defensive blocks with maximal efficiency.